The Impact of Virtual Reality Hypnosis on Pain and Anxiety Caused by Trauma: Lessons Learned from a Clinical Trial. Issue 2 (3rd April 2022) - Wiechman, Shelley A.; Jensen, Mark P.; Sharar, Sam R.; Barber, Jason K.; Soltani, Maryam; Patterson, David R.
ABSTRACT: This randomized, controlled trial tested the impact that hypnosis delivered through immersive virtual reality technology on background pain, anxiety, opioid use, and hospital length of stay in a sample of patients hospitalized for trauma. Participants were randomly assigned to receive either virtual-reality-induced hypnosis, virtual reality for distraction, or usual care during the course of their hospitalization. Mean number of treatment sessions was 3. A total of 153 patients participated in the study. Results indicated no significant differences between the experimental and control conditions on any outcome measures. This study used an early version of virtual reality technology to induce hypnosis and highlighted several important lessons about the challenges of implementation of this technology and how to improve its use in clinical settings.